Regulating pre-performance psychobiosocial states with music - Middleton, Thierry (2016)
The present study aimed to investigate the effects of music on swimmers’ pre-performance psychobiosocial states. We involved a purposeful sample of competitive swimmers (N = 17) in a 5-week intervention grounded in the individual zones of optimal functional (IZOF) model. Multiple findings were revealed. The first showed that pre-performance psychobiosocial states were predictive of subsequent performance. This was revealed by a high number of significant differences found between best and worst performance across modalities. Second, swimmers improved their ability to regulate pre-performance states through the use of music. This was shown through evidence that no significant differences were found across modalities between best and worst performance for experimental group swimmers, while significant differences existed for control group swimmers. The third major finding was that the use of music had a positive impact on swimmers’ perceived effectiveness of pre-performance routines. This was revealed by a significant difference being found between experimental and control group swimmers on a subjective rating of pre-performance routines in time trials one and four. Furthermore, swimmers’ qualitative reports indicated that music use was made more purposeful due to the introduction of a music intervention. Also found was that the two main types of music used were classified as ‘pump-up’ and ‘motivational’. The current study provides preliminary evidence in support of the use of music during pre-performance routines to enhance the athletes’ performance states. Athletes are encouraged to engage in the process of carefully selecting music in accordance with previously delineated optimal individualized performance related state profiles.